Optimized BM3D for mmWave massive MIMO channel estimation - Jiafeng QIU (Dianxin kexue)
Focused on the issue in which beamspace channel estimation is challenging for mmWave massive MIMO system when the number of RF chains is limited,a channel estimation scheme based on optimized BM3D was proposed.The MIMO channel matrix based on 3D lens-based can be regarded as a 2D natural image,and the image reconstruction technology was integrated into the channel estimation.BM3D was considered as one of the most accurate algorithms for image denoising ,while the grouping was realized by block-matching and collaborative filtering was accomplished by shrinkage in a 3D transform domain.Utilizing the sparsity feature of the channel and the clustering feature of the paths,the BM3D algorithm was optimized in order to improve the performance.Simulations are provided to show that proposed optimized BM3D scheme can achieve satisfactory accuracy in all considered SNR regions.